Studies on respiratory disorders - Jindal, Surinder K.; Biswal, Shyam; Barnes, Peter J.; Pawankar, Ruby; Ganguly, Nirmal K. (Oxidative Stress in Applied Basic Research and Clinical Practice, 2014)
Studies on Respiratory Disorders considers the whole panorama of oxidative damage in different respiratory disorders for the review of clinician and laboratory investigators and makes diverse information available in a single volume.  This volume provides a comprehensive review of numerous studies on the role of oxygen and nitrogen species in lung diseases; it also discusses the potential role of anti-oxidants in their treatment.  The contents are organized into three sections along fairly broad classifications: I.  General introductory chapters on oxidant stress; general considerations related to reactive oxygen and nitrogen species; the role of exhaled breath condensate and other volatile compounds as exhaled biomarkers of inflammation;  II. Oxidative stress in different groups of respiratory disorders such as pulmonary infections (viral, bacterial and tuberculosis);  airway diseases such as chronic obstructive pulmonary diseases, air pollution, allergies and asthma; miscellaneous lung diseases (e.g., interstitial diseases, sarcoidosis, asbestosis, respiratory muscle dysfunction, pulmonary hypertension and cancer); and III., Anti-oxidant drugs. These final chapters on anti-oxidant drugs including the mimics (such as traditional herbs) provide a critical review of the available information on their success and failure.  Studies on Respiratory Disorders is an important addition to the Oxidative Stress in Applied Basic Research and Clinical Practice series and is essential reading  for those treating or researching treatment for respiratory disorders.